Experience in Teaching OOAD to Various Students - Danijela BOBERIC-KRSTICEV; Danijela TESENDIC (Informatics in Education, 2013)
The paper elaborates on experiences and lessons learned from the course on object-oriented analyses and design at the Faculty of Sciences, Novi Sad. The course on OOAD is taught to students of computer science and to the students of mathematical programme. Conclusions made in this paper are based on results of students' assignments as well as results of conducted survey. In the paper we identify a set of issues concerning teaching modelling and UML. It is noticed that difficulties in mastering OOAD arise primarily from the absence of appropriate real case studies from the field of designing information systems. In order to overcome this problem, students worked on their own homework projects which include all phases of software development. Concerning the results of survey it is noticed that OOAD course should be taught in different manners regarding previous knowledge of students. Suggestions how to teach OOAD to students of computer science and to students of other programmes are given in this paper.